تأثير جودة الخدمة المقدمة من الجامعات السعودية على رضا طلابها: منهج تسويقي - Alhudaithy, Abdullatif (مجلة العلوم الإدارية و الإقتصادية, 2014)
Service quality, informed by a detailed understanding of students’ needs and demands, has become an increasingly important concept in the marketing of higher educational institutions worldwide. Currently, however, the Saudi higher education sector, which has grown rapidly since its formal inception in 1975, is receiving criticism that its teaching provision is inadequate and its research output limited. To throw light on this situation, and remedy to some extent the dearth of extant research in this area, this paper examines Saudi students’ satisfaction with the quality of various aspects of their university experience and the relationship of those aspects to their perceived learning outcomes, by means of a survey based on the SERVQUAL model carried out among 364 students attending 5 universities in Saudi Arabia. Among the findings, it was discovered that although instructor characteristics, course content and classroom environment influenced students’ perceived learning outcomes to a similar degree, only instructor and classroom environment influenced student satisfaction; course content was seen as less important than either, albeit the curricula offered for humanities subjects were generally perceived as more satisfactory in terms of primary knowledge provided than those offered for sciences. Satisfaction ratings were lowest for instructors and for the notion that, given the choice of repeating their studies, respondents would choose the same university. These latter results in particular suggest that at least some of the criticism leveled at Saudi universities may be valid, and that there is much the universities can do to improve their service quality and thus attract more students.